Bio-Matrix Pot Addition Enhanced the Vegetation Process of Iron Tailings by Pennisetum giganteum - Liu, Yihao; Yu, Jinyang; Wang, Zuyu; Penttinen, Petri; Yu, Xiumei; Zhao, Ke; Ma, Menggen; Xiang, Quanju; Gu, Yunfu; Liu, Hanjun; Zhang, Xiaoping; Chen, Qiang (Frontiers in Microbiology, 2022)
The barrenness of large mine tailing sand reservoirs increases the risks for landslides and erosion that may be accompanied with transfer of contaminants into the surrounding environment. The tailing sand is poor in nutrients which effectively complicates the vegetation process. We investigated direct planting of Pennisetum giganteum into tailing sand using two pit planting methods: the plants were transplanted either directly into pits filled with soil or into soil filled biomatrix pots made of organic material. After growing P. giganteum in iron tailing sand for 360 d, the dry weight of the plants grown in the biomatrix pot (T2) were approximately two-fold higher than those of the plants grown in soil placed directly into the sand (T1). At 360 d, the OM content in the soil below the pit was lowest in the not planted treatment (T0) and highest in T2, the available N (AN) contents were higher in T1 and T2 than in T0, and the available P and K contents were highest in T2. At 360 d, the Shannon diversity of the soil microbial communities was higher in T1 and T2 than in T0, and the community compositions were clearly separated from each other. The profiles of predicted C cycle catabolism functions and N fixation related functions in T1 and T2 at 360 d were different from those in the other communities. The results showed that P. giganteum grew well in the iron tailing sand, especially in the biomatrix pot treatment, and the increased the nutrient contents and changes in microbial communities indicated that using the biomatrix pot in planting had potential to improve the vegetation process in iron tailing sands effectively.